2022
DOI: 10.2460/ajvr.22.08.0127
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic twist technique has the best overall artifact profile when comparing three laparoscopic hepatic cup biopsy techniques for dogs

Abstract: OBJECTIVE To determine the difference in histologic artifacts and morphologic diagnosis among 3 laparoscopic cup biopsy forceps techniques and wedge hepatic samples. ANIMALS Cadavers of 20 client-owned dogs following euthanasia for unrelated reasons between January 3 and July 29, 2021. PROCEDURES Four biopsy techniques were performed from the margin of 3 liver lobes/dog. Laparoscopic techniques used 5-mm cup biopsy forceps to obtain biopsy samples by pulling the forceps forcefully caudally to free a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 15 publications
1
11
4
Order By: Relevance
“…This is similar to the results of a recent study that described a twisting technique where 90% of samples had sharp edges and 65% of samples had mild to moderate tearing artifacts. 11 Although the TP technique resulted in greater tissue crush artifact, the median crush artifact was mild (grade 1), and a morphological diagnosis was still obtained in all tissue samples, so this finding may not be clinically relevant.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This is similar to the results of a recent study that described a twisting technique where 90% of samples had sharp edges and 65% of samples had mild to moderate tearing artifacts. 11 Although the TP technique resulted in greater tissue crush artifact, the median crush artifact was mild (grade 1), and a morphological diagnosis was still obtained in all tissue samples, so this finding may not be clinically relevant.…”
Section: Discussionmentioning
confidence: 96%
“…This may explain our lower agreement compared to a recent study that examined three samples using each technique and found excellent agreement for the diagnosis. 11 Having three veterinary surgeons with differing surgical experience perform the liver biopsies may also have influenced the size and quality of samples obtained. However, liver biopsies are routinely performed by veterinarians of varying experience, which might lead to some variability with any liver biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations